Extranodal Marginal Zone Lymphoma of Mucosa-Associated Lymphoid Tissue With Amyloid Deposition - Russell J.H. Ryan; J. Mark Sloan; A. Bernard Collins; Jaleh Mansouri; Noopur Raje; Lawrence Zukerberg; Judith A. Ferry (2011)
Abstract Extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT) lymphoma is a mature B-cell neoplasm that typically follows an indolent clinical course. Amyloid deposition associated with MALT lymphoma is uncommon. We describe the clinical and pathologic features of 20 cases of MALT lymphoma and associated amyloid deposition across diverse primary sites. Frozen section immunofluorescence performed on 4 cases suggests that these deposits are a localized form of AL amyloid. Clinical follow-up was available for 15 patients. Amyloid deposits distant from the initial site occurred in 5 cases, always at sites also involved by the underlying lymphoma. No definitive evidence of systemic amyloidosis affecting the heart, kidneys, or liver was present in any patient. Given the generally indolent clinical behavior of MALT lymphomas with associated amyloid, we do not recommend extensive follow-up testing for systemic amyloidosis or more aggressive therapy than would be indicated for other MALT lymphomas of similar clinical stage.